Scientific Transformation of Islamic Boarding Schools through Role of Alums the Islamic Education Study Program - Efendy, Rustan; Rahman, Ali; Karim, Abdul Rahim (Al-Hayat: Journal of Islamic Education, 2023)
This study aims to reveal the existence and role of alums of the Islamic Religious Education study program in carrying out scientific transformations in Islamic boarding schools. The research location is the As-Salman Allakuang Darud Da'wah wal Ershad (DDI) Islamic boarding school, Sidenreng Rappang Regency. This study uses a qualitative research approach with a case study type. Data collection techniques used participant observation, semi-structured interviews, focusing on crucial informants, namely alums of the Islamic Religious Education study program who had served since 2016 at the DDI As-Salman Allakuang Islamic boarding school, as well as documentation studies. The data analysis technique used the interactive analysis technique of Miles, Huberman, and Saldana. Testing the validity of the data is done by going through the credibility, dependability, confirmability, and transferability tests. The results showed that alums of the Islamic Religious Education study program from the Parepare State Islamic Institute played an essential role in the scientific transformation of the DDI As-Salman Allakuang Islamic boarding school since 2016. Their role is seen in four ways: 1) Maximizing the functions and duties as educators by carrying out the mandate, 2) Equipping students with millennial-era skills through structured activities, 3) Strengthening self-potential and sensitivity to contemporary realities for students, and 4) Intensifying the internalization of values and ethics by carrying out recitation, coaching, and cadre training to strengthen the basis of morality Students. The value of these findings underscores the importance of alums, the relevance of education to the needs of the times, social responsibility as educators, and strengthening identity and self-potential in the context of Islamic religious education in Islamic boarding schools.